2020
DOI: 10.18586/msufbd.784635
|View full text |Cite
|
Sign up to set email alerts
|

Al2O3 Nanopartikülleri İçeren Çok Duvarlı Karbon Nanotüpler Kullanılarak Su Bazlı Sondaj Çamurlarının Reolojik ve Filtrasyon Özelliklerinin Geliştirilmesinde Yenilikçi Bir Yaklaşım: Deneysel Araştırma

Abstract: Sondaj çamuru kuyu tabanın temizlenmesi, yüksek basınçlı formasyonları kontrol etme, korozyona karşı koruma gibi önemli görevleri yerine getiren hayati derece öneme sahip bir akışkandır. Bu çalışmada Al 2 O 3 NP/ÇDKNT; kimyasal buhar biriktirme (CVD) yöntemi ile üretilmiş, X-Işını Fotoelektron Spektroskopisi (XPS) ve Geçirimli Elektron Mikroskobu (TEM) ile karakterize edilmiş, ardından su bazlı sondaj çamurlarına farklı oranlarda (0.001 -0.01% k/h) eklenmiştir. Hazırlanan sondaj çamurlarının plastik viskozites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In the last step, the graphite in the form of steam is fed into the furnace and carbon deposition occurs on the metal nanoparticles as a result of catalytic decomposition at 2000 °C and 100 torr pressure. 34,35 20 ml of 1.0 mM HAuCl 4 was added into a 50 ml volumetric flask on a stirred hot plate. While stirring, 2 ml of Na 3 C 6 H 5 O 7 .2H 2 O (1%) was slowly added to the gold precursor solution at 65 °C.…”
Section: Production Of Multi-walled Carbon Nanotubes (Mwcnts)-mentioning
confidence: 99%
“…In the last step, the graphite in the form of steam is fed into the furnace and carbon deposition occurs on the metal nanoparticles as a result of catalytic decomposition at 2000 °C and 100 torr pressure. 34,35 20 ml of 1.0 mM HAuCl 4 was added into a 50 ml volumetric flask on a stirred hot plate. While stirring, 2 ml of Na 3 C 6 H 5 O 7 .2H 2 O (1%) was slowly added to the gold precursor solution at 65 °C.…”
Section: Production Of Multi-walled Carbon Nanotubes (Mwcnts)-mentioning
confidence: 99%
“…According to the study's findings, the gel strength values (10 s and 10 min) increased by 27% and 166.6%, the plastic viscosity value grew by 85.7%, the apparent viscosity value was 113%, the yield point value was 187.5%, and the water loss value dropped by 6%. The impacts of Al2O3NPs/ MWCNTs on water-based drilling mud were examined by Özkan et al 16 The work results showed that the filtering loss value dropped by 13.8%, the cake thickness value increased by 18.5%, the PV value increased by 85.7%, the AV value by 41.8%, the YP value by 20%, and the 10 s and 10 min values grew by 16.6% and 11%, respectively. Furthermore, as the literature study demonstrates, metal oxide nanoparticles such SiO 2 , TiO 2 , Fe 2 O 3 , CuO, and ZnO are also utilized to enhance the filtration and rheological characteristics of water-based drilling muds.…”
mentioning
confidence: 99%
“…As a result of the study, it was determined that the plastic viscosity value increased by 85.7%, the apparent viscosity value was 113%, the yield point value was 187.5%, the gel strength values (10 s and 10 min) increased by 275% and 166.6%, and the water loss value decreased by 6%. Özkan et al (2020) 15 investigated the effects of Al 2 O 3 NPs/MWCNTs on water-based drilling mud. In the results of working; they observed that the PV value increased by 85.7%, the AV value by 41.8%, the YP value by 20%, the 10 s and 10 min values increased by 16.6% and 11%, respectively, the filtration loss value decreased by 13.8%, and the cake thickness value increased by 18.5%.…”
mentioning
confidence: 99%